Plang Sampah Sebagai Media Edukasi Lingkungan: Upaya Meningkatkan Kesadaran Masyarakat Tentang Bahaya Sampah Tidak Terurai: (Kuliah Kerja Nyata Nagari Pandam Gadang, Universitas Negeri Padang) - Ika Parma Dewi; Ahmad Fadhel Haq; Kasih Intan Sahira; Abil Arqham; Nahdia Latifah; Hajidah Aisyah Iwanina; Vivi Kesuma Dewi; Rizky Ananda; Rafi Aryatama (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2026)
Waste management is a major challenge in environmental conservation in Indonesia. One innovative approach that can be implemented is the use of informative waste signs as a visual educational medium for the public. Waste signs are information boards placed in strategic locations to provide knowledge about the types of waste, their environmental impacts, and the decomposition time of various materials. The Community Service Program (KKN) of Padang State University (UNP) has implemented this concept by creating educational boards containing information on waste decomposition time, ranging from waste that decomposes in 50–100 years to waste that does not decompose at all. This article aims to examine the concept, benefits, and effectiveness of waste signs as a community-based environmental education instrument. The methods used include field observation and a qualitative descriptive approach. The results of the study indicate that waste signs can increase public awareness of the importance of proper waste management. Thus, this medium has the potential to be a simple yet effective educational tool in supporting sustainable environmentally friendly behavior.